Report of the Ad Hoc Committee on the Indian Ocean: 6 July 2023 - United Nations Department for General Assembly; Conference Management (United Nations, 2023)
This is the official record submitted to the United Nations General Assembly on the Ad Hoc Committee on the Indian Ocean.